Antimicrobial Treatment to Impair Expansion of Abdominal Aortic Aneurysm (AAA): A Systematic Review of the Clinical Evidence - Bergqvist, David; Lindeman, Johannes H.N.; Lindholt, Jes S.; Bjorck, Martin (Current Vascular Pharmacology, 2013)
Antimicrobial treatment to attenuate expansion of abdominal aortic aneurysm has been suggested, especially with the focus on Chlamydophila. In this systematic literature review only four randomized trials were identified. In two small studies there is an indication of an effect of roxithromycin. In conclusion, however, more studies are needed, and they must be properly sized based on power calculations as well as antimicrobially relevant. Such trials are on the way both in Europe and the US, the results being awaited with interest.
Keywords: tetracycline